2006
DOI: 10.1111/j.1365-2966.2005.09960.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved HCN/HNC linelist, model atmospheres and synthetic spectra for WZ Cas

Abstract: We build an accurate data base of 5200 HCN and HNC rotation–vibration energy levels, determined from existing laboratory data. 20 000 energy levels in the Harris et al. linelist are assigned approximate quantum numbers. These assignments, lab‐determined energy levels and Harris et al. energy levels are incorporated in to a new energy level list. A new linelist is presented, in which frequencies are computed using the lab‐determined energy levels where available, and the ab initio energy levels otherwise. The n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
135
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(136 citation statements)
references
References 30 publications
1
135
0
Order By: Relevance
“…We found that among the complete set of 105 molecules contained in the chemical model, these are the most abundant ones in all cases and will therefore dominate the spectral modulation. The wavelength-dependent cross sections for these absorbing molecules were computed using line lists from ExoMol (Barber et al 2006(Barber et al , 2014Harris et al 2006;Yurchenko et al 2011Yurchenko et al , 2013Tennyson & Yurchenko 2012), HITRAN (Rothman et al 2013), and HITEMP (Rothman et al 2010). Note that the mean molecular weight of each atmospheric layer is coupled to the mixing ratio of all 105 molecules.…”
Section: Synthetic High-resolution Transmission Spectramentioning
confidence: 99%
“…We found that among the complete set of 105 molecules contained in the chemical model, these are the most abundant ones in all cases and will therefore dominate the spectral modulation. The wavelength-dependent cross sections for these absorbing molecules were computed using line lists from ExoMol (Barber et al 2006(Barber et al , 2014Harris et al 2006;Yurchenko et al 2011Yurchenko et al , 2013Tennyson & Yurchenko 2012), HITRAN (Rothman et al 2013), and HITEMP (Rothman et al 2010). Note that the mean molecular weight of each atmospheric layer is coupled to the mixing ratio of all 105 molecules.…”
Section: Synthetic High-resolution Transmission Spectramentioning
confidence: 99%
“…The eigenenergies published in Ref. 25 have been used for this analysis. When the assignment work was started there was no reason to try to construct a better PES and to recalculate the rovibrational eigenenergies.…”
Section: Approximate Twofold Rotational Degeneracy Of the Hcn Anmentioning
confidence: 99%
“…In fact all 45 000 eigenvalues up to the isomerisation barrier have already been calculated. 24,25 molecular system only parity and total angular momentum are exact quantum numbers and the eigenenergies have to be labeled with vibrational quantum numbers in an assignment procedure. This work presents the results from the rotational assignment of all rovibrational eigenenergies up to the isomerisation barrier.…”
Section: Approximate Twofold Rotational Degeneracy Of the Hcn Anmentioning
confidence: 99%
“…To get precise estimates of T eff , additional model atmospheres were produced that resulted in a grid spacing of ΔT = 10 K. All the main molecular opacities typical of C-stars were included: CO (Goorvitch & Chackerian 1994), C 2 (Querci et al 1974), HCN (Harris et al 2006), CN (Jørgensen 1997) in the form of line lists, and C 2 H 2 and C 3 (Jorgensen et al 1989) as OS data. CS is not included due to the lack of line lists and OS data.…”
Section: Hydrostatic Modelsmentioning
confidence: 99%